Drug toxicity in children: paediatric randomised controlled drug trials and global child health - Nor Aripin, Khairun Nain Bin (2010)
Concern with potential toxicity due to the widespread use of unlicensed and off label drugs in children has led to regulatory changes aimed to strengthen the evidence base for paediatric drugs. This thesis examines paediatric randomised controlled trials (RCTs), the highest level of evidence, and assesses them in relation to global child health.